Strategic leadership in Malaysia education: A systematic literature reviews - Zakariah, Nur Diyana; A. Ghani, Muhammad Faizal; Radzi, Norfariza Mohd (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2023)
Strategic leadership is a critical issue for school leaders. Over the past few decades, strategic leadership studies in fields other than education have been implemented, but there is still a lack of studies related to strategic leadership in education. The purpose of this systematic literature review (SLR) is to provide a comprehensive overview of research related to strategic leadership in Malaysia, identifying any gaps in the literature as a reference for future research. This study was conducted systematically and the review was based on the PRISMA (Reporting Standards for Systematic Evidence Synthesis) method. This study selected articles using two leading databases, namely Scopus and Web of Science, and one supporting database, Google Scholar. A systematic review process, eligibility and exclusion criteria, review process steps (identification, screening, eligibility) and data analysis were conducted. The results show that there is limited literature on strategic leadership and from the literature there are three primary dimensions that are stated from a throughout the school and educational institutions viewpoint in Malaysia: (i) mission, vision and values, (ii) futuristic thinking skills, and (iii) leading a change strategy. Further research is also expected to develop a strategic leadership model of teacher leaders in the Malaysian context. This is important to expand research related to strategic leadership in a more complex way to gain a better understanding of this construct especially in Malaysia.